Pneumococcal meningitis in the newborn period in a prevaccination era: a 10-year experience at a tertiary intensive care unit - Baş, Ahmet Yağmur; Demirel, Nihal; Aydın, Mustafa; Zenciroglu, Ayşegül; Tonbul, Alparslan; Tanır, Gönül (The Turkish Journal of Pediatrics, 2011)
There are few data with respect to pneumococcal meningitis in neonates. Epidemiological aspects, clinical features and outcomes in newborn infants diagnosed with pneumococcal meningitis were evaluated in this study. Nineteen newborn infants in a neonatal intensive care unit diagnosed with culture-proven community-acquired bacterial meningitis between January 1999 and December 2008 were reviewed, and of them, eight patients were diagnosed as pneumococcal meningitis. Overall, among 10,186 hospitalized newborn infants, 132 community-acquired sepsis/meningitis cases (1.3%) were suspected, and blood cultures were performed in all, while cerebrospinal fluid (CSF) cultures could be performed in 124 cases. Rate of blood culture positivity was 45%. Nineteen (15.3%) of 124 were diagnosed as culture-proven community-acquired bacterial meningitis, which was confirmed by CSF growth. Eight (42.1%) of 19 had pneumococcal meningitis. In pneumococcal cases, abundant Gram-positive diplococci were seen on CSF smear and Streptococcus pneumoniae was isolated from CSF cultures. All isolates were susceptible to penicillin and third-generation cephalosporins. Irritability (n: 7), poor sucking (n: 7) and fever (n: 6) were the principal findings on the initial physical examination. Of all patients with pneumococcal meningitis, four were initially given cefotaxime plus amikacin treatment, and the remaining four were initially given cefotaxime plus ampicillin plus vancomycin. Antibiotic treatment in two patients was revised during their clinical course. Additionally, in three patients, vancomycin and ampicillin was discontinued on the third day when antibiogram of CSF cultures revealed penicillin sensitivity. Overall, mortality in pneumococcal meningitis was 50%. In the surviving patients, two had epilepsy, one sensorineural hearing loss, and two mental-motor retardation. Pneumococcal meningitis was the leading cause of community-acquired neonatal meningitis in our patients. Immunization against pneumococcal disease in developing countries would be beneficial for public health and for newborn infants.